Die Neubestimmung des Staat-Kirche-Verhältnisses in den neuen Ländern durch Staatskirchenverträge: zu den Möglichkeiten und Grenzen des staatskirchenvertraglichen Gestaltungsinstruments - Anke, Hans Ulrich (Jus Ecclesiasticum, 2000)
After German reunification, the new German federal states had to restructure their relationship to the various religious communities, and thus they signed 17 contracts with the Holy See, the regional churches and Jewish associations. In this work, the author presents and systematizes the content of these state contracts. He explains the 4 basic functions of contracts between the state and religious communities as being to organize their cooperation, to support religious activities, to consolidate the existing guarantees and to lay down ecclesiastical duties.